Development of a universal dual-bolus injection scheme for the quantitative assessment of myocardial perfusion cardiovascular magnetic resonance - Ishida, Masaki; Schuster, Andreas; Morton, Geraint; Chiribiri, Amedeo; Hussain, Shazia; Paul, Matthias; Merkle, Nico; Steen, Henning; Loßnitzer, Dirk; Schnackenburg, Bernhard; Alfakih, Khaled; Plein, Sven; et al. (Journal of cardiovascular magnetic resonance, 2011)
The dual-bolus protocol enables accurate quantification of myocardial blood flow (MBF) by first-pass perfusion cardiovascular magnetic resonance (CMR). However, despite the advantages and increasing demand for the dual-bolus method for accurate quantification of MBF, thus far, it has not been widely used in the field of quantitative perfusion CMR. The main reasons for this are that the setup for the dual-bolus method is complex and requires a state-of-the-art injector and there is also a lack of post processing software. As a solution to one of these problems, we have devised a universal dual-bolus injection scheme for use in a clinical setting. The purpose of this study is to show the setup and feasibility of the universal dual-bolus injection scheme.
Gesehen am 04.07.2022